Pengaruh Promosi Terhadap Minat Pasien Rawat Inap di Rumah Sakit Ibu dan Anak Santa Anna Bandar Lampung - Johanes P Kumagaya; Titus Tomi (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2022)
This research is conducted to find out the effect of promotion on the interests of inpatients at RSIA Santa Anna Hospital. This research uses a direct field research method with the object of research is RSIA Santa Anna Hospital Bandar Lampung for the interpretation of results using a percentage. The results of the research showthat the promotion carried out by RSIA Santa Anna Hospital Bandar Lampung has effects on the increasing of the interest of inpatients in the hospital. Some elements of activitiesreally need to get more attention in order to increase the interest of inpatients. From the results of a simple regression coefficient calculation, the promotion contribution is 0.368, and is significant so that it meets the criteria and can be used to predict the significance of the X variable (Promotion) to the Y variable (Interest). The results of the coefficient of determination (R2) that is, the effect of promotion on interest is 32.2% while the remaining 67.8% is influenced by other factors not examined by researchers From the simple regression coefficient test it can be concluded that Ha is accepted. Therefore, it means that there is a significant influence between promotion and interest of inpatients. Therefore, in this research, it can be concluded that promotion greatly influences the interest of inpatients at the Santa Anna Mother and Child Hospital.